Placebo-Controlled Effectiveness of Idiopathic Normal Pressure Hydrocephalus Shunting: A Randomized Pilot Trial. Issue 3 (25th March 2023) - Luciano, Mark; Holubkov, Richard; Williams, Michael A.; Malm, Jan; Nagel, Sean; Moghekar, Abhay; Eklund, Anders; Zwimpfer, Thomas; Katzen, Heather; Hanley, Daniel F.; Hamilton, Mark G.
Abstract : BACKGROUND: Multiple prospective nonrandomized studies have shown 60% to 70% of patients with idiopathic normal pressure hydrocephalus (iNPH) improve with shunt surgery, but multicenter placebo-controlled trial data are necessary to determine its effectiveness. OBJECTIVE: To evaluate the effectiveness of cerebrospinal fluid shunting in iNPH through comparison of open vs placebo shunting groups at 4 months using a pilot study. METHODS: Patients were randomized to a Codman Certas Plus valve (Integra LifeSciences) set at 4 (open shunt group) or 8 ("virtual off"; placebo group). Patients and assessors were blinded to treatment group. The primary outcome measure was 10-m gait velocity. Secondary outcome measures included functional scales for bladder control, activities of daily living, depression, and quality of life. Immediately after 4-month evaluation, all shunts were adjusted in a blinded fashion to an active setting and followed to 12 months after shunting. RESULTS: A total of 18 patients were randomized. At the 4-month evaluation, gait velocity increased by 0.28 ± 0.28 m/s in the open shunt group vs 0.04 ± 0.17 m/s in the placebo group. The estimated treatment difference was 0.22 m/s ([ P = .071], 95% CI −0.02 to 0.46). Overactive Bladder Short Form symptom bother questionnaire significantly improved in open shunt vs placebo ( P = .007). The 4-month treatment delay did not reduce the subsequent response to active shunting, nor did it increase the adverse advents rate at 12 months. CONCLUSION: This multicenter, randomized pilot study demonstrates the effectiveness, safety, and feasibility of a placebo-controlled trial in iNPH, and found a trend suggesting gait velocity improves more in the open shunt group than in the placebo group.